Object Video Tracking using a Pan-Tilt-Zoom System - A. Taha, Mohammed; F. Babiker, Sharief (University of Khartoum Engineering Journal, 2022)
This paper implements object video tracking system that represents object location in subsequent video frames. A closed-circuit television (CCTV) camera mounted on a rotating system is used for capturing video while the object of interest always kept at the centre of the screen. Three tracking algorithms were selected and implemented: template matching, contour matching and optical flow. Measures of their accuracy and speed were taken for comparison. The software was implemented in a personal computer with C# programming language, with the aid of EmguCV which is a wrapper for OpenCV, a famous image processing library. The system implemented for this study is able to successfully track a rigid body, discernible from the background objects with size up to 400×300 pixel for the Phase Alternate Line (PAL) system of 720×576 pixel frame size. Tracking was stable even with the existence of rotation and scaling. Some faults were observed when occlusion was present or when the target was moving with a speed faster than that of the rotation system of 30 degrees/s horizontal and 15 degrees/s vertical.